Clinical studies on submicroscopic subtelomeric rearrangements: a checklist. Issue 3 (1st March 2001) - de Vries, B B A; White, S M; Knight, S J L; Regan, R; Homfray, T; Young, I D; Super, M; McKeown, C; Splitt, M; Quarrell, O W J; Trainer, A H; Niermeijer, M F; et al.
Abstract : BACKGROUND: Submicroscopic subtelomeric chromosome defects have been found in 7.4% of children with moderate to severe mental retardation and in 0.5% of children with mild retardation. Effective clinical preselection is essential because of the technical complexities and cost of screening for subtelomere deletions. METHODS: We studied 29 patients with a known subtelomeric defect and assessed clinical variables concerning birth history, facial dysmorphism, congenital malformations, and family history. Controls were 110 children with mental retardation of unknown aetiology with normal G banded karyotype and no detectable submicroscopic subtelomeric abnormalities. RESULTS: Prenatal onset of growth retardation was found in 37% compared to 9% of the controls (p<0.0005). A higher percentage of positive family history for mental retardation was reported in the study group than the controls (50% v 21%, p=0.002). Miscarriage(s) were observed in only 8% of the mothers of subtelomeric cases compared to 30% of controls (p=0.028) which was, however, not significant after a Bonferroni correction. Common features (>30%) among subtelomeric deletion cases were microcephaly, short stature, hypertelorism, nasal and ear anomalies, hand anomalies, and cryptorchidism. Two or more facial dysmorphic features were observed in 83% of the subtelomere patients. None of these features was significantly different from the controls. Using the results, a five item checklist was developed which allowed exclusion from further testing in 20% of the mentally retarded children (95% CI 13-28%) in our study without missing any subtelomere cases. As our control group was selected for the "chromosomal phenotype", the specificity of the checklist is likely to be higher in an unselected group of mentally retarded subjects. CONCLUSIONS: Our results suggest that good indicators for subtelomeric defects are prenatal onset of growth retardation and a positive family history for mental retardation. These clinical criteria, in addition to features suggestive of a chromosomal phenotype, resulted in the development of a five item checklist which will improve the diagnostic pick up rate of subtelomeric defects among mentally retarded subjects.